Finance-growth nexus revisited for some Asian countries - Mukhopadhyay, Bidisha; Pradhan, Rudra P.; Feridun, Mete (Routledge Journals, Taylor & Francis Ltd, 2011)
This article investigates the causal relationship between financial development and economic growth for Thailand, Indonesia, Malaysia, the Philippines, China, India and Singapore for the period between 1979 and 2009, using Johansen cointegration tests and vector error correction models. The results suggest that in the case of Indonesia, Singapore, the Philippines, China and India financial development leads to economic growth, whereas in the case of Thailand there exists a bidirectional causality between these variables. The results further suggest that in the case of Malaysia financial development does not seem to cause economic growth.
Keywords: financial development; economic growth; multivariate VAR